Conceptual design of the EU DEMO EC-system: main developments and R&D achievements. (2nd August 2017) - Granucci, G.; Aiello, G.; Alberti, S.; Avramidis, K.A.; Braunmüller, F.; Bruschi, A.; Chelis, J.; Franck, J.; Figini, L.; Gantenbein, G.; Garavaglia, S.; Grossetti, G.; et al.
Abstract: For the development of a DEMOnstration Fusion Power Plant the design of auxiliary heating systems is a key activity in order to achieve controlled burning plasma. The present heating mix considers electron cyclotron resonance heating (ECRH), neutral beam injection (NBI) and ion cyclotron resonance heating (ICRH) with a target power to the plasma of about 50 MW for each system. The main tasks assigned to the EC system are plasma breakdown and assisted start-up, heating to L-H transition and plasma current ramp up to burn, MHD stability control and assistance in plasma current ramp down. The consequent requirements are used for the conceptual design of the EC system, from the RF source to the launcher, with an extensive R&D program focused on relevant technologies to be developed. Gyrotron : the R&D and Advanced Developments on EC RF sources are targeting for gyrotrons operating at 240 GHz, considered as optimum EC Current Drive frequency in case of higher magnetic field than for the 2015 EU DEMO1 baseline. Multi-purpose (multi-frequency) and frequency step-tunable gyrotrons are under investigation to increase the flexibility of the system. As main targets an output power of significantly above 1 MW (target: 2 MW) and a total efficiency higher than 60% are set. The principle feasibility at limits of a 236 GHz, conventional-cavity and, alternatively, of a 238 GHz coaxial-cavity gyrotron are under investigation together with the development of a synthetic diamond Brewster-angle window technology. Advanced developments are on-going in the field of multi-stage depressed collector technologies. Transmission line (TL) : different TL options are under investigation and a preliminary study of an evacuated quasi-optical multiple-beam TL, considered for a hybrid solution, is presented and discussed in terms of layout, dimensions and theoretical losses. Launcher : remote steering antennas have been considered as a possible launcher solution especially under the constraints to avoid movable mirrors close to the plasma. With dedicated beam tracing calculations, the deposition locations coverage and the wave absorption efficiency have been investigated, considering a selection of frequencies, injection angles and launching points. An option for the EC system structure is proposed in clusters, in order to allow the necessary redundancy and flexibility to guarantee the required EC power in the different phases of the plasma pulse. Number and composition of the clusters are analysed to have high availability and therefore maximum reliability with a minimum number of components.